Delegation Decisions in Finance - Felix Holzmeister; Martin Holmen; Michael Kirchler; Matthias Stefan; Erik Wengström (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
We run an online experiment with finance professionals and subjects from the general population (clients) to examine drivers and implications of clients' delegation decisions. We find that clients favor delegation to investment algorithms, followed by delegation to finance professionals with aligned incentives and lastly to those with fixed incentives. We also show that trust in investment algorithms or money managers (finance professionals), respectively, and clients' propensity to shift blame on others increases the likelihood of delegation, whereas own decision-making quality is associated with a decrease. In measuring the implications of clients' delegation decisions, we report high variability among finance professionals' perceptions of clients' preferred risk levels. We show that this results in overlaps in portfolio risk across risk-levels of clients, indicating problems of risk communication between clients and their money managers.
Keywords: C93; G11; G41; 330; Experimental finance; finance professionals; delegated decision-making